2011
DOI: 10.1021/ja203057z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Cleavage of HIV RRE RNA by Rev-Coupled Transition Metal Chelates

Abstract: A series of compounds that target reactive metal-chelates to the HIV-1 Rev Response Element (RRE) mRNA have been synthesized. Dissociation constants and chemical reactivity toward HIV RRE RNA have been determined and evaluated in terms of reduction potential, coordination unsaturation, and overall charge associated with the metal-chelate-rev complex. Ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), diethylenetriaminepentaacetic acid (DTPA), and 1,4,7,10-tetraazacyclo-dodecane-1,4,7,10-tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 39 publications
5
103
1
Order By: Relevance
“…Oxidation of RNA is likely facilitated by the high oxidation state Cu 3+ and formation of intermediate ROS, a characteristic of Cu-ATCUN complexes. [2, 1924] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of RNA is likely facilitated by the high oxidation state Cu 3+ and formation of intermediate ROS, a characteristic of Cu-ATCUN complexes. [2, 1924] …”
Section: Discussionmentioning
confidence: 99%
“…[12] Incorporation of a reactive metal-binding domain allows for the irreversible inactivation of a target protein or RNA and the potential for multiple turnover to irreversibly modify and inactivate many copies of a target, resulting in a therapeutic effect at lower dosage. [3] Previous work has shown that the tetrapeptide sequence YrFK-amide (where the arginine is in the d -conformation) binds to stem loop IIb (SLIIb) of the Internal Ribosomal Entry Site (IRES) of Hepatitis C Virus (HCV) RNA [4] and that incorporation of a metal-binding ATCUN [5] (amino terminal copper and nickel binding, XXH, where X ≠ P) motif results in catalytic degradation of the target RNA under oxidative conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To gauge the reactivity of the Fe(II) complexes in air under reducing conditions analogous to those in blood, we used ascorbate as a biologically relevant reductant (E o = − 66 mV [16,40]. The fact that [Fe(L4)] 2+ has the lowest ascorbate consumption suggests that the eight donor groups protect the Fe(II) center and inhibit redox cycling.…”
Section: Reactivity Of the Fe(ii) Complexes Towards Oxygen And Peroxidementioning
confidence: 99%
“…[72] The targeted cleavage of RRE by a metallopeptide bearing an amino-terminal copper binding motif connected the binding domain of Rev has also been reported. [73,74] Boronic acids are known to covalently link to the 2'-and/or 3'-hydroxyl group of ribose in a reversible manner, under physiological conditions. [75] As a consequence, it can be expected that compounds bearing boronic acid moieties could bind to RNA with improved selectivity over DNA thanks to an additional interaction with the 2'-OH of ribonucleic acids.…”
Section: Rev-rre Interactionmentioning
confidence: 99%